A review of high‐resolution microscopic ghost imaging with a low‐dose pseudothermal light. (2nd August 2021) - Sun, Z.; Tuitje, F.; Spielmann, C.
Summary: High‐resolution imaging is an important issue in various fields of scientific researches and engineering applications. Pseudothermal ghost imaging is one of the subfields of quantum imaging, providing new capabilities beyond conventional imaging methods. Also, it can provide a new viewpoint of imaging physical mechanisms. In this review, we explain the major ideas of pseudothermal ghost imaging, restricting the very important case of high‐resolution imaging. We analyse the strategies which can significantly improve the image quality in pseudothermal ghost imaging. It may apply for merging it with common optical imaging methods in the extreme ultraviolet (XUV) or X‐ray spectral regime for driving the applications to a wider audience in bioscience and nano‐physics. Key points: Ghost imaging, based on multiplexing, can help overcome specific kinds of noise. It can offer a way to alleviate the irreversible damage to the sample, because the object does not interact with the CCD camera. Pseudothermal light sources have a substantially higher flux, so the performance of the pseudothermal ghost imaging system can exceed those based upon parametric down‐conversion sources. XUV and X‐ray radiography are invaluable tools for the analysis of biological samples and in nano‐physics. The pseudothermal ghost imaging can easily be transferred into the XUV and X‐ray regime without a lens, whereas parametric down‐conversion is restricted to the visible and infrared range. The main drawbacks of pseudothermal ghost imaging are longer acquisition times and the large number of measurements required for image recovery. At present, the resolution of microscopic ghost imaging has never reached the level of traditional microscopic imaging.